2017
DOI: 10.1016/j.bbrc.2017.09.141
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA expression profiles in different severity EV71-infected hand foot and mouth disease patients

Abstract: Enterovirus 71 (EV71) is associated with the severe hand foot and mouth disease (HFMD) outcomes, however the host-virus interaction mechanism and the pathogenesis remain poorly understood. Long non-coding RNAs (lncRNAs) are involved in variety physiological and pathological processes, but the functions of lncRNAs in EV71 infection remain elusive. Here we profiled the expression of lncRNAs in peripheral blood mononuclear cells (PBMCs) from EV71-infected mild patients, severe patients as well as the healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A recent study showed that hsa-miR-23b could inhibit host EV71 replication through downregulation of the EV71 VP1 protein [ 25 ]. However, prior to the present study the regulation roles of lncRNA in EV71 infection-induced pathogenesis were rarely reported [ 26 , 27 ]. It was previously reported that results from microarray-based transcriptional assays are less accurate and not fully capable of predicting novel lncRNAs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that hsa-miR-23b could inhibit host EV71 replication through downregulation of the EV71 VP1 protein [ 25 ]. However, prior to the present study the regulation roles of lncRNA in EV71 infection-induced pathogenesis were rarely reported [ 26 , 27 ]. It was previously reported that results from microarray-based transcriptional assays are less accurate and not fully capable of predicting novel lncRNAs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to systematically study the regulatory effects of the neurotropic enterovirus A71 (EVA71) infection on lncRNAs, Yin et al performed a comprehensive analysis of EVA71‐infected rhabdomyosarcoma (RD) cells and observed differential expression of greater than 4800 lncRNAs . Similarly, Meng et al identified 8541 differentially expressed lncRNAs in EVA71‐infected human peripheral blood mononuclear cells . Also, using the RNA sequencing (RNA‐Seq) technique, Shi et al identified a total of 760 and 1210 lncRNAs that were upregulated and downregulated, respectively, in RD cells infected with Coxsackievirus A16 (CVA16).…”
Section: Differential Expression Of Lncrnasmentioning
confidence: 99%
“…The lncRNA expression profiles in EV71 infection have been determined, and the differentially expressed lncRNAs were suggested involved in viral pathogenesis explored by lncRNA-mRNA coexpression network Meng et al, 2017;Yin et al, 2013). The altered lncRNAs in EV71 infection were thought to regulate immune and inflammatory responses, protein binding, as well as host component biogenesis and metabolism and could serve as disease progression signatures , Yin et al, 2013.…”
Section: Figurementioning
confidence: 99%